The Influence of Demographics and Religiosity Factors on Islamic Financial Literacy - Riris Aishah Prasetyowati; Djubaedi Yunus; Ahmad Rodoni; Amilin Amilin (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
The purpose of this study is to examine the influence of demographics and religiosity on Islamic financial literacy. Using a quantitative approach with a Likert scale questionnaire-based survey method, the population was 2800 respondents of Sharia Bank customers in Jakarta, Bogor, Depok, Bekasi, Tangerang, Surabaya, Semarang, and other cities in Indonesia. The accidental method was used and obtained a selected sample size of 400 respondents, which were analyzed using the Partial Least Square (PLS) method. The novelty shows that dimensions that do not support the significant effect of demographic and religiosity variables on Islamic financial literacy are income, moral, and experience if associated with moral hazard because they are supported by manifestations related to morality. The results of hypothesis testing show that there is a significant effect of demographics on religiosity, a significant effect of demography on Islamic financial literacy, and a significant effect of religiosity on Islamic financial literacy.